Strategi Digitalisasi UMKM dalam Meningkatkan Daya Saing dan Kinerja Usaha di Era Ekonomi Digital - Syifa Namira Nasution; Steven I.S.M Marbun; Trinita Siringoringo; Vita olivia Silalahi (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
Digital transformation has become an important agenda for the development of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia in line with the increasing role of the digital economy in the national economic structure. This study aims to examine the digitalization strategies implemented by MSMEs, identify the obstacles faced in the digitalization process, and analyze their relationship with business performance. The research method used is a literature review by examining journal articles, official reports, and relevant scientific publications published in the last five years. The results of the study show that MSME digitalization strategies generally focus on increasing digital literacy, utilizing e-commerce platforms, optimizing social media as a marketing tool, and strengthening managerial support and organizational culture. The implementation of these strategies correlates with increased sales, operational efficiency, and market reach expansion. However, the digitization process still faces limitations in terms of resources, infrastructure, and organizational readiness. This study emphasizes that digitization is a strategic opportunity for MSMEs if it is supported by inclusive policies and capacity building for business actors.